PERBANDINGAN NILAI LAJU ENDAP DARAH (LED) ANTARA METODE WESTERGREN DENGAN METODE MIKRO ESR PADA PENDERITA TUBERKULOSIS PARU - Silvia Hidriyah; Mellysa Rahmita; Citra Trisna (Jurnal Medikes (Media Informasi Kesehatan), 2018)
One of the diseases that evoke an inflammatory reaction and affect the value of ESR is Pulmonary Tuberculosis. ESR examination suggested by ICSH is Westergren method. But there are many instances where the patient's venous blood sampling is so difficult that the blood obtained is small. One of the modification methods that can be used for ESR examination is the Micro ESR method. The purpose of this research is to know the comparison of ESR values ​​using Westergren and Micro ESR methods. The material used for this research is 3.8% citrate blood derived from 30 samples of patients with Pulmonary Tuberculosis at Krakatau Medika Hospital Cilegon. The average result of ESR Pulmonary Tuberculosis with Westergren method was 41,83 mm/hr and the mean value of ESR Pulmonary Tuberculosis with Micro ESR method was 33,03 mm/hr. The result of this research is processed by statistical test using Paired Sample T Test and got significance value (sig. 2-tailed) = 0,016. This value is smaller than the value of α = 0.05 which means there is a difference between the two examination variables, so the Micro ESR method could not be used for patients with Pulmonary Tuberculosis.